2022
DOI: 10.48550/arxiv.2203.05732
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Great Balls of FIRE I: The formation of star clusters across cosmic time in a Milky Way-mass galaxy

Abstract: The properties of young star clusters formed within a galaxy are thought to vary in different interstellar medium (ISM) conditions, but the details of this mapping from galactic to cluster scales are poorly understood due to the large dynamic range involved in galaxy and star cluster formation. We introduce a new method for modeling cluster formation in galaxy simulations: mapping giant molecular clouds (GMCs) formed self-consistently in a FIRE-2 MHD galaxy simulation onto a cluster population according to a G… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 124 publications
(226 reference statements)
0
8
0
Order By: Relevance
“…To fully model clusters, one possibility for cosmological or galactic simulations is to include the cluster evolution separately using a theoretical or empirical model (Pfeffer et al 2018) or by separately evolving a sample of clusters (Grudić et al 2022). An alternative approach is to model the full population of stars with Nbody dynamics (Fujii et al 2021;Rieder et al 2022;Liow et al 2022), even if the gas resolution is low, thus achieving the same resolution in the stars as individual cluster simulations.…”
Section: Introductionmentioning
confidence: 99%
“…To fully model clusters, one possibility for cosmological or galactic simulations is to include the cluster evolution separately using a theoretical or empirical model (Pfeffer et al 2018) or by separately evolving a sample of clusters (Grudić et al 2022). An alternative approach is to model the full population of stars with Nbody dynamics (Fujii et al 2021;Rieder et al 2022;Liow et al 2022), even if the gas resolution is low, thus achieving the same resolution in the stars as individual cluster simulations.…”
Section: Introductionmentioning
confidence: 99%
“…Star clus-ters form and evolve within their host galaxies across cosmic times (e.g Adamo et al 2020a). State-of-art cosmological simulations follow cluster formation and evolution during galaxy assembly like the Milky Way and M31 (e.g., Grudić et al 2022;Reina-Campos et al 2022, among the latest). These simulations agrees that the peak formation of massive star clusters (masses > 10 5 M ) is around redshift 3 (Reina-Campos et al 2019) in these Milky-Way like progenitors.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, compressive tides and/or shock compression due to galaxy mergers are likely to have played an important role in GC formation (Renaud et al 2015;Kim et al 2018b;Lahén et al 2019). Improving upon tagging methods, Grudić et al (2022b) applied a cluster formation model derived from their GMC simulations (Grudić et al 2021) to a Milky Way-like galaxy, and showed that the clus-ter mass-size relation observed in nearby star-forming galaxies can be explained if denser GMCs form clusters with high efficiency. However, the detailed formation processes have not yet been rigorously investigated.…”
Section: Introductionmentioning
confidence: 99%